Surfactin reduces the adhesion of food-borne pathogenic bacteria to solid surfaces - Nitschke, M.; Araujo, L. V.; Costa, S. G. V. A. O. [UNESP]; Pires, R. C.; Zeraik, A. E.; Fernandes, A. C. L. B.; Freire, D. M. G.; Contiero, Jonas [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Aims:To investigate the effect of the biosurfactants surfactin and rhamnolipids on the adhesion of the food pathogens Listeria monocytogenes, Enterobacter sakazakii and Salmonella Enteritidis to stainless steel and polypropylene surfaces.Methods and Results:Quantification of bacterial adhesion was performed using the crystal violet staining technique. Preconditioning of surfaces with surfactin caused a reduction on the number of adhered cells of Ent. sakazakii and L. monocytogenes on stainless steel. The most significant result was obtained with L. monocytogenes where number of adhered cells was reduced by 10(2) CFU cm(-2). on polypropylene, surfactin showed a significant decrease on the adhesion of all strains. The adsorption of surfactin on polystyrene also reduces the adhesion of L. monocytogenes and Salm. Enteritidis growing cells. For short contact periods using nongrowing cells or longer contact periods with growing cells, surfactin was able to delay bacterial adhesion.Conclusions:The prior adsorption of surfactin to solid surfaces contributes on reducing colonization of the pathogenic bacteria.Significance and Impact of the Study:This is the first work investigating the effect of surfactin on the adhesion of the food pathogens L. monocytogenes, Ent. sakazakii and Salm. Enteritidis to polypropylene and stainless steel surfaces.
Keywords: bacterial adhesion; biofilms; biosurfactants; rhamnolipids; surfactin